Histopathology and clinical course of MOG‐antibody‐associated encephalomyelitis. (14th January 2015) - Spadaro, Melania; Gerdes, Lisa Ann; Mayer, Marie C.; Ertl‐Wagner, Birgit; Laurent, Sarah; Krumbholz, Markus; Breithaupt, Constanze; Högen, Tobias; Straube, Andreas; Giese, Armin; Hohlfeld, Reinhard; Lassmann, Hans; et al.
Abstract: We present histological, MRI, and clinical features of an adult patient with relapsing encephalomyelitis and antibodies against myelin oligodendrocyte glycoprotein (MOG). Furthermore, we report molecular details of the recognized epitope that is specific for human MOG. A brain biopsy revealed multiple sclerosis (MS)‐type II pathology. Some features overlapped with both MS and neuromyelitis optica spectrum disorders (NMOSD), whereas others were distinct from both MS and NMOSD. Immunoadsorption and rituximab induced clinical stabilization. This case contributes a new, so far missing link in the emerging spectrum of MOG‐antibody‐associated encephalomyelitis.